The paradox of gender and depression in Indian geriatric outpatients: a study revealing higher depressive symptoms among males - Sharma, Shweta; Gupta, Abha; Satyam; Chaudhary, Garima (International Journal of Research in Medical Sciences, 2026)
Background: Epidemiological data from Western populations show a higher prevalence of depression in elderly women, attributed to biological and psychosocial factors. However, this pattern is challenged by sociocultural contexts that shape gender roles and aging experiences. The geriatric gender gap in depression within Indian clinical populations remains inadequately characterized. This study investigated gender-based differences in the prevalence and correlates of depressive symptoms in geriatric outpatients in Northern India. Methods: A hospital-based, cross-sectional study was conducted over six months in the Medicine Outpatient Department of a tertiary-care hospital. A total of 100 consecutive patients (60 men, 40 women) aged ≥60 years were enrolled. Depressive symptoms were assessed using the 15-item Geriatric Depression Scale (GDS-15). Between-group comparisons and gender-stratified correlation analyses were performed. Results: The prevalence of clinically significant depressive symptoms (GDS-15 ≥5) was significantly higher in men (68.3%) compared to women (40.0%) (p=0.004). The mean GDS-15 score was also significantly elevated in men (5.4±2.3) relative to women (4.1±2.3) (p=0.004). Among men, depression scores correlated positively with coronary artery disease (r=0.32, p=0.01); no significant clinical correlates were identified in women. Conclusions: This study reveals a significant reversal of the typical gender disparity in geriatric depression within a North Indian clinical sample. The findings suggest that culturally constructed masculine roles, compounded by age-related stressors like retirement, may predispose elderly men to higher depression risk. This underscores the need for gender-sensitive mental health screening tailored to aging populations in India.